La eficiencia de la revocatoria del mandato como mecanismo de participación ciudadana - Torres Barreno, Ramiro Sebastián (2024)
ABSTRACT: The research addresses the revocation of mandate as an effective mechanism of citizen participation, a constitutional right that was implemented for the first time in the 1998 Political Constitution and was ratified in articles 5, 6 and 145 of the 2008 Constitution. The main purpose The purpose of this study is to determine whether the revocation of mandate really fulfills its function as an effective mechanism for citizen participation. The research approach used combines quantitative and qualitative methods, as data were collected both numerically and non-numerically. This study is characterized by being non-experimental, cross-sectional and descriptive. Several methods were applied, such as inductive-deductive, legal-analytical, legal comparison, documentary analysis, surveys, and data analysis and processing through the exploratory factor analysis method, the calculation of Cronbach's Alpha and the use of descriptive statistics. The object of study constitutes: documents, books, scientific articles, regulations, laws, judicial rulings and resolutions related to the efficiency of the revocation of mandate and citizen participation. In addition, Ecuadorian citizens between the ages of 18 and 65 who have access to the Internet and are willing to participate in the study were included. A digital survey was applied to 384 people through random probabilistic sampling. The research instrument used reached a Cronbach's Alpha coefficient of 0.996. The exploratory factor analysis identified 4 main factors and 22 items close to 1. The results obtained indicate that the majority of citizens do not perceive the revocation of mandate as an effective mechanism of citizen participation due to various factors. The analysis of the flow chart showed that the revocation process is cumbersome and long, with difficulties for the common citizen, directly and indirectly influencing the inefficiency of this process as a mechanism for citizen participation. The analysis of two judicial rulings also revealed the inefficiency of the citizen participation process in the revocation of mandate, caused by several factors, such as the contradiction of rules and powers, excess regulations and citizen confusion due to lack of information. truthful, transparent and accessible online. To improve participation in relation to the recall of mandate, it is essential to explore citizens' perceptions and work on the transparency and effectiveness of the recall process. Keywords: revocation of mandate, citizen participation, availability of resources, efficiency